To bear witness : a journey of healing and solidarity - Cahill, Kevin M. (International humanitarian affairs (Unnumbered), 2013)
For more than fifty years, Dr. Cahill has been helping to heal the world, as a leading specialist in tropical medicine and as a driving force in humanitarian assistance and relief efforts around the globe. In this revised and expanded edition, he chronicles extraordinary achievements of compassion and commitment. Bringing together a rich selection of writings, he crafts a fascinating memoir of a life devoted to others. The book includes front-line reports from places under siege Lebanon, Somalia, Sudan, Nicaragua, Gaza, and Ireland; there are also visionary essays from the origins of the AIDS.